Perceived Social Cohesion in Ukraine: Diversity and Attitudes - Deineko, Oleksandra; Aasland, Aadne; Filippova, Olga; Muradyan, Olena (East/West, 2023)
This article demonstrates the ways in which social cohesion as a “sense of togetherness” is progressing within Ukrainian society—a society that is striving to escape the post-Soviet model as it undergoes the processes of state- and nation building and democratic development. This study draws on a national population survey and applies cluster analysis to identify homogeneous groups of the population in terms of their social-cohesion perceptions and behaviours. Six clusters are identified: distrustful, disunited, ambivalent, tolerant, connected, and declarative. The authors establish the composition of each cluster in relation to socio-economic, socio-demographic, ethnocultural, and attitudinal characteristics. Their research questions the relevance of institutional trust as a social-cohesion indicator in the context of the specific conditions of transitional societies. The authors submit that trust in political institutions might strengthen social cohesion at the level of society without necessarily corresponding to individually oriented indicators of social cohesion, such as civic and political participations. This paper sheds light on the weaknesses of the methodological approach advanced by Joseph Chan and colleagues. With the application of cluster analysis in the present study, one finds that the horizontal dimension of social cohesion is particularly well suited for use in cross-cultural studies. By contrast, the vertical dimension emerges as more contextual, requiring greater attention to the specificities of a given political regime. This paper proposes the existence of social-cohesion zigzags displaying an ambivalent state of perceptional schemes where the highest cohesion scores in some indicators are accompanied by the lowest ones in others within the same representative group. This study confirms the complexity and multi-level nature of social cohesion in transitional societies.